The Effect of The Flipped-Guided Inquiry Learning (FGIL) Learning System Toward Student Outcomes on Chemical Reaction Rate - Firma Yulianis; Mawardi Mawardi (Universitas Negeri Padang, 2022)
This study aims to determine the effect of flipped-classroom based on guided inquiry learning system on students' learning outcomes of class XI students in SMA Negeri 8 Padang. The subject in this study were students of class XI MIPA 2 as the experiment class and students of class XI MIPA 1 as the control class using purposive technique sampling. The type of research is experimental quasi-equivalent control study design groups. The technique of data analysis used is two means similarity test (t-test). The object of this study is students’ learning outcomes on reaction rate material. The instruments of this study is used in the formative test consists of the initial test (pretest) and the final test (posttest) with 17 numbers of multiple choice questions based on the learning objectives. The difference between the pretest and posttest scores for experiment class is 48,77 while for the control class is 41,18. Data analysis shows that the subject are normally distributed and homogeneous so the t-test can be done, and the value of thitung obtained is 1,71. This proves that the learning outcomes between experiment class and control classes have significant differences. Based on data analysis, it shows that flipped-classroom based on guided inquiry learning system has proven the improve students' learning outcomes significantly.